1965
DOI: 10.1063/1.1713940
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Study of Gold-Gallium Arsenide Schottky Barriers

Abstract: Departures from the theoretical behavior of a Schottky barrier are reported in the case of gold on gallium arsenide. It is shown that the empirical introduction of a single temperature-independent parameter takes care of all the observed departures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
57
0
1

Year Published

1968
1968
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(70 citation statements)
references
References 7 publications
11
57
0
1
Order By: Relevance
“…The increase in ideality factor with decreasing temperature is known as the T 0 effect and was first reported by Padovani and Sumner [2]. The Schottky barrier height (SBH), F I2V measured by the I2V technique for TE decreases with decreasing temperature and increasing doping level, while the SBH F C2V measured by the capacitance-voltage ðC2VÞ method remains constant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in ideality factor with decreasing temperature is known as the T 0 effect and was first reported by Padovani and Sumner [2]. The Schottky barrier height (SBH), F I2V measured by the I2V technique for TE decreases with decreasing temperature and increasing doping level, while the SBH F C2V measured by the capacitance-voltage ðC2VÞ method remains constant.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the SBD parameters are determined over a wide range of temperatures and doping concentrations in order to understand the nature of the barrier and the conduction mechanism. Thermionic emission (TE) theory is normally used to extract the SBD parameters [1][2][3][4][5][6][7], however, there have been several reports of certain anomalies [4,[7][8][9] at low temperatures. The ideality factor and barrier height determined from the forward bias current-voltage ðI2VÞ characteristics on the basis of the TE mechanism were found to be a strong function of temperature and doping concentration [5,[9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The origins of inhomogeneous Schottky barrier theory dates back to the 1960's when non-linearities within the classic Richardson plot hindered the extraction of the SBH and Richardson constant (A * * ). 21 This became known as the T 0 effect whereby it was found that adding a temperature constant into the thermionic emission equation the plot would linearise and aid in the extraction of the SBH. We now know that at an inhomogeneous interface, the SBH will rise and the ideality factor fall as the temperature is increased due to the junction current becoming dominated by fewer low SBH patches [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Many solutions were suggested to return linearity to the plots [21][22][23] before the link with inhomogeneities was made 9,11,15,24 . Two techniques exist to modify the classic Richardson plot to extract the barrier height, taking into account SBH lowering due to an inhomogeneous contact.…”
Section: Introductionmentioning
confidence: 99%
“…The current-voltage characteristics of Au/GaAs, Cr/Si, Ni/Si, and Au/Si [39][40][41] exhibited a so-called T 0 anomaly: explanation of the experimental data required the addition of a constant temperature T 0 to the absolute temperature in the significant exponential part of the characteristic. From model calculations by Levine [42,43], it appeared that this T 0 anomaly defined by exponential surface-state energy distribution with a width that was related to the value of T 0 .…”
Section: Discussionmentioning
confidence: 99%